Socialization of Children with Down Syndrome: Developmental, Familial, and Educational Influences – A Narrative Review - Catama, Bryan V (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
Socialization plays a vital role in the development of children. It encompasses the process of acquiring social norms, behaviors, and necessary skills to build relationships and establish one’s identity. Children with Down syndrome (DS) face unique socialization challenges due to cognitive, communicative, and behavioral impairments. This narrative review examines the interplay of developmental, familial, and educational factors influencing the socialization of children with DS. Cognitive and language delays, emotional and behavioral difficulties, and motor skill deficits are analyzed for their impact on social interactions. Familial support, particularly parental attitudes and sibling dynamics, is also considered. The review assesses the impact of educational environments on peer interactions and social competence, highlighting the benefits of inclusive settings and specialized support. Finally, the review identifies intervention strategies that can enhance social engagement and suggests areas for future research to improve the quality of life for children with DS.